Spatial heterogeneity and local oscillation phase drifts in individual-based simulations of a prey-predator system - Waniewski, Jacek; Jędruch, Wojciech (Zielona Góra: Uniwersytet Zielonogórski)
Individual-based simulations of a simple prey-predator system of Lotka-Volterra type were carried out on a tessellation of identical squares with discrete time steps. The particles representing individuals moved freely along (roughly) straight lines with constant (on the average) velocity, and changed their movement during a collision with another particle.
Keywords: rey-predator system; individual-based simulations; spatial heterogeneity; oscillation phase drift; parameter estimation